AIRLINE CREW PAIRING PROBLEM: A LITERATURE REVIEW - Deveci, Muhammet; Demirel, Nihan Cetin (VARAZDIN DEVELOPMENT & ENTREPRENEURSHIP AGENCY, 2015)
The airline crew scheduling problem is one of the most important problems by all airline companies that can affect cost structure, time constraints etc. substantially. In terms of cost structure, crew costs come second in scale after fuel costs. The airline crew scheduling problem, therefore, is the key for developing solutions in order to decrease operational costs (total crew cost). Unlike the fuel expenses, operational costs can be controlled. The airline crew scheduling (ACS) is generally divided into crew pairing problem and crew rostering (or crew assignment) problem. Crew pairing and crew rostering are considered separate but related problems. The aim of the airline crew pairing problem (CPP) is to come up with a set of minimal cost crew pairings by covering all flight legs. In the rostering problem, these parings are assigned to specified crew members. In this paper, we review the literature on crew scheduling problems for airlines. Our aim is to present a comprehensive review, emphasizing recent studies and solution methodologies.
Keywords: Airline crew scheduling; Crew pairing; Crew rostering; Set partitioning; Public Administration